PENERAPAN SISTEM INFORMASI KALENDAR TANAM ( SI KATAM) MENDUKUNG PENINGKATAN INDEKS PERTANAMAN PADI KABUPATEN INDRAGIRI HULU - Anis Fahri; Syuryati Syuryati; Ade Yulfida; Rachmiwati Yusuf (DINAMIKA PERTANIAN, 2019)
ABSTRACT Integrated Planting Calendar Information System becomes a necessity, which is expected to increase agricultural yields and can reduce crop losses due to drought and floods. Besides that an information that is summarized in one data-base becomes a need to get various information in a quick time. This planting calendar provides complete information for farmers. These operational guidelines are established at the community and sub-district levels. Planting Calendar Information System as an important tool in adjusting cropping patterns with climate change. Deliver information about the direction, strategies, and policies of the agricultural sector on climate change in the form of a road map to stakeholders and related parties. This paper aims to find out the application of water resources and climate in supporting the improvement of Indragiri Hulu Regency's rice crop index. The methodology used is through field observations and secondary data collection. The Research and Development Agency has developed adaptive technology with climate change, namely the Integrated Planting Calendar Information System (KATAM). The results showed that referring to the Recapitulation of Rice Potential Calendar for Indragiri Hulu Regency in the planting season MH 2017/2018 and MK April - September 2018 it was known that the area of ​​rice planting was 5.029 ha with a Planting Index of 269%. The recommended potential for SI Katam Integrated rice was 862 ha wider than the existing planting area of ​​4.167 ha with an IP value of 118%.